Identifying the Dimensions and Components of Health Tourism with a Strategic Business Orientation Approach Using Thematic Analysis - Chatrooz, Azadeh; Azad, Naser; Naami, Abdullah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The main objective of this article is to identify the dimensions and components of health tourism with a strategic business orientation approach using thematic analysis. Method: The research method is qualitative. In addition to documentary studies, the thematic analysis technique with MAXQDA12 software was used to identify factors and components. The population in this study consisted of all experts in the field of tourism and health, as well as senior managers with extensive experience and a high track record in the field of tourism and health, after which theoretical saturation was achieved following 14 interviews. The interviews lasted between 75 to 120 minutes. Ultimately, basic, organizing, and comprehensive themes were extracted. Findings: Five factors (developmental, strategic, infrastructural, limiting, and outcomes) and 20 dimensions (organizing themes) and 43 components and 208 indicators for health tourism with a strategic business orientation were extracted. Conclusion: The results showed that the majority of experts believed that health tourism with a strategic business orientation faces issues in structural areas and domestic policies, and these factors have the most significant impact in this regard.